YOU CAN'T DO BUSINESS WITH THE DEATH - Kasim, Halim (EMERALD GROUP PUBLISHING LTD, 2021)
An Innocent Merriment - A Medieval Song about the Plague also sheds light on the COVID-19 epidemic period as an epidemic song. Companies are not in solidarity; they are trying to replace artificial intelligence with labour. Short work, more rest, more time for children, strong immune system, happy families are easier with artificial intelligence. Using artificial intelligence against labour condemns us to collective stupidity. The slogan of capitalism has been discussed in the prime centres of globalisation. For the financial centre, globalisation is the unimpeded circulation of money across borders, the transfer of its earnings whenever it wants, and not encountering national barriers. Now it is said that there should be customs for goods and a mobility barrier for people. People will not accept this without injuring their conscience. The Wat Tyler rebellion, which erupted after the Black Death following the Great Famine, was the birth pain of the bourgeoisie. The war against the mystical, irrational world of the Middle Ages strengthened the bourgeoisie. The irrational ideas of the bourgeoisie, which today emulate the aristocracy with admiration, open the way for despots; the bourgeoisie is almost preparing its own end. The bourgeoisie led the great transformations by preaching respect for labour in the footsteps of thinkers such as Wat Tyler, A. Smith, J. Locke. However, the leadership cannot be sustained with the feudal capitalist mood: `Liberty, equality, fraternity' is still alive, except for the leader! The understanding of `the better always can be in a shorter time' in the economy made humanity unhappy and filled its time. Based on the household economy, the environmentally friendly core economy can be a solution by opening the door to street workers and disadvantaged groups, as the flood of solidarity in every corner of our planet adds strength and morale to our resilience.
Keywords: Globalisation; core economy; solidarity; medieval; Wat Tyler; feudal capitalist; Business & Economics; Public, Environmental & Occupational Health; Public Administration